Hydrophilic polymer embolism identified in brain tumor specimens following Wada testing: A report of 2 cases - Goodwill, Vanessa S.; Brandel, Michael G.; Steinberg, Jeffrey A.; Beaumont, Thomas L.; Hansen, Lawrence A. (Free Neuropathology, 2021)
Hydrophilic polymers are commonly used as coatings on intravascular medical devices. As intravascular pro-cedures continue to increase in frequency, the risk of embolization of this material throughout the body has become evident. These emboli may be discovered incidentally but can result in serious complications includ-ing death. Here, we report the first two cases of hydrophilic polymer embolism (HPE) identified on brain tu-mor resection following Wada testing. One patient experienced multifocal vascular complications and diffuse cerebral edema, while the other had an uneventful postoperative course. Wada testing is frequently per-formed during preoperative planning prior to epilepsy surgery or the resection of tumors in eloquent brain regions. These cases demonstrate the need for increased recognition of this histologic finding to enable fur-ther correlation with clinical outcomes.